Effectiveness of European Open Science Policies on Improving Economic Competitiveness - Kárász, István (GILE Journal of Skills Development, 2025)
This study evaluates the European Commission’s strategy to enhance innovation and competitiveness through the research, innovation and development (R&I&D) sector, with a particular focus on Open Science (OS). Recognising OS as a global megatrend with promising societal impacts, the paper explores its economic implications, which to date remain insufficiently evidenced. The research examines investments made during Horizon 2020 and Horizon Europe, highlighting successes and ongoing challenges, such as the EU’s fragmented policy environment, regulatory hurdles, and the underutilisation of research by the private sector. The analysis draws on key findings from the European Innovation Scoreboard and insights from the Letta and Draghi reports, which underscore declining EU competitiveness in the global R&I&D landscape, particularly compared to China and the U.S. The paper identifies critical obstacles, including low industry engagement, the lack of standardised practices, and disparities in member states’ capacities and disciplinary differences. Not only does it emphasise the necessity for more effective governance structures, harmonised policies, and investment strategies tailored to industry and end-user needs, but it also highlights the need for new, collaborative skills and readiness to collaborate from all disciplines and stakeholders. Recommendations align with the Budapest Declaration on the New European Competitiveness Deal, advocating for a robust Single Market, improved data integration, and increased private-sector investment. By addressing these barriers, the EU can leverage the R&I&D sector to regain its competitive edge, enhance innovation-driven economic growth, and deliver impactful solutions to societal challenges.